Energy projection analysis of solar energy for water pump system using gridline power with focus on control system - Ahmad Syafiq, Shiro (2013)
Robots are important technology that greatly increases the productivity. In robotics a manipulator is a device used to manipulate materials without direct contact for dealing with radioactive or bio-hazardous materials, or they were used in inaccessible places. In this project, a single link flexible manipulator is used. It will be attached to the DC motor. When DC motor is rotated to certain angle, the single link also will rotate on x-axis. The vibration amplitude is produce directly from the speed of the rotation of the dc motor when it stops. A study to counter this problem had been made to control and maintains the accurate position of the single flexible manipulator. Matlab is software that will be use to conduct the study. The objective of this project to control vibration on the single link flexible manipulator using Proportional Integral Derivative (PID) Controller. Active Force Control (AFC) controller also will be used with PID Controller to compensate the vibration. The system without controller will be compare with the system with controller by the graph. The combination of AFC and PID give the best result in rise time, settling time and steady state error. The proposed controller schemes manage to produce output that able to follow the desired trajectory from 68.2 percent overshoot to zero percent overshoot.